Vaccinia Virus Infection Requires Maturation of Macropinosomes. (6th May 2015) - Rizopoulos, Zaira; Balistreri, Giuseppe; Kilcher, Samuel; Martin, Caroline K.; Syedbasha, Mohammedyaseen; Helenius, Ari; Mercer, Jason
<x xml:space="preserve">Abstract</x> The prototypic poxvirus, vaccinia virus (VACV), occurs in two infectious forms, mature virions (MVs) and extracellular virions (EVs). Both enter HeLa cells by inducing macropinocytic uptake. Using confocal microscopy, live‐cell imaging, targeted RNAi screening and perturbants of endosome maturation, we analyzed the properties and maturation pathway of the macropinocytic vacuoles containing VACV MVs in HeLa cells. The vacuoles first acquired markers of early endosomes [Rab5, early endosome antigen 1 and phosphatidylinositol(3)P]. Prior to release of virus cores into the cytoplasm, they contained markers of late endosomes and lysosomes (Rab7a, lysosome‐associated membrane protein 1 and sorting nexin 3). RNAi screening of endocytic cell factors emphasized the importance of late compartments for VACV infection. Follow‐up perturbation analysis showed that infection required Rab7a and PIKfyve, confirming that VACV is a late‐penetrating virus dependent on macropinosome maturation. VACV EV infection was inhibited by depletion of many of the same factors, indicating that both infectious particle forms share the need for late vacuolar conditions for penetration. <inline-graphic xlink:href="ark:/27927/pgj1m9qb375" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />